Moyamoya Syndrome or Fibromuscular Dysplasia? A Complex Case of Pediatric Stroke - Marques, Joana (2022)
Moyamoya disease and fibromuscular dysplasia are two arteriopathies that can cause stroke in pediatric age. These have been proposed to have the same pathological basis and cases of moyamoya disease with extracranial involvement have overlapping clinical features to those seen in fibromuscular dysplasia. A heterogenous genetic component is thought to play a part in both and some genes have shown simultaneous association with the two diseases. Some aspects of clinical management are also similar. We report a case of a 6-month-old infant with a rare and extensive multivessel disease that first presented as ischemic stroke and severe and refractory hypertension. A chromosomal translocation and distinctive facial characteristics were also present. Genetic investigation is underway, and it might help to better tailor therapy and define prognosis.